A Single Case Study of Cupping Therapy in AVABAHUK (Frozen Shoulder). - Panchal, Sonal; Patel, Jigna; kazi, Wasim; Ninama, Divya (Asian Journal of Pharmaceutical Research and Development, 2023)
Pain has been described by the International Association for the Study of Pain as “an unpleasant sensory and emotional experience associated with actual or potential tissue damage”. Shoulder pain is one of the most common health problems encountered in the general population.Shoulder pain is a common symptom, in especially in office workers. In developed countries, approximately twothirds of people experience shoulder pain. This disorder occurs most frequently in the middle-aged population and more often in females than in males. A majority of the acute shoulder sufferers obtain spontaneous relief within days or weeks, although approximately 10% of acute shoulder pain suffers experience the condition as chronic or persistent. Conventional treatments such as medications and surgery were not always effective, and may have serious adverse effects. Frozen shoulder is a chronic aseptic inflammation caused by injury and degeneration of shoulder capsule and periarthritic soft tissue (including ligaments, muscles, tendons, synovial sacs, etc.). [i]Cupping is gaining popularity in physical medicine due to its ease of use, lack of side effects, and pain relief. This study looked at the efficacy of cupping therapy for treating shoulder pain. Cupping therapy (CT) is a traditional Chinese medical (TCM) treatment which has been practiced for thousands of years. The World Health Organization’s (WHO) definition of cupping is a therapeutic method involving the application of suction by creating a vacum. This is typically done using fire in a cup or jar on the dermis of the affected part of the body.[ii] In this case study a patient diagnosed with AVABAHUK (Frozen Shoulder) was treated with a WET CUPPING THERAPY. After completion of cupping therapy significant relief was observed in symptoms.